Salvage cystectomy and ileal conduit urinary diversion as a last‐line option for benign diseases—perioperative safety and postoperative health‐related quality of life. Issue 5 (3rd May 2021) - Volz, Yannic; Eismann, Lennert; Pfitzinger, Paulo L.; Jokisch, Jan‐Friedrich; Schulz, Gerald; Rodler, Severin; Buchner, Alexander; Schlenker, Boris; Stief, Christian G.; Kretschmer, Alexander
Abstract: Aims: Radical cystectomy and urinary diversion impact various dimensions of patients' health‐related‐quality‐of‐life (HRQOL). Yet, less is known about salvage cystectomy as a last‐line option for treatment‐refractory benign diseases. Therefore, our aim is to provide HRQOL data from a contemporary cohort of open salvage cystectomies for benign conditions. Methods: Fifty‐four consecutive patients were enrolled in one single tertiary referral center. Analysis was limited to patients undergoing urinary diversion via ileal conduit (IC). Complications were assessed via Clavien–Dindo‐scale. HRQOL was measured using the validated European Organization for Research and Treatment of Cancer QLQ‐C30 and QLQ‐BLM30 questionnaire. HRQOL QLQ‐C30 domains were measured preoperatively and up to 3 years postoperatively. Longitudinal changes were analyzed using Friedman's rank test. Primary endpoint was good general HRQOL based on QLQ‐C30 global health status (GHS). Multivariate analysis was performed using logistic regression models with a step‐wise backward selection procedure. Results: Longitudinal analysis of HRQOL subdomains revealed significantly improved pain ( p  = .005) and fatigue ( p  = .002) scores as well as improved social functioning ( p  = .038). Furthermore, general HRQOL (GHS scores) improved significantly during the follow‐up period (28.0 vs. 50.6 [36 months], p  = .045). In multivariate analysis, the indication for salvage cystectomy could not be identified as an independent predictor for good general HRQOL. We observed a total number of 10 (41.7%) high‐grade (Clavien ≥III) 90 day‐complications. Limitations include limited follow‐up rates at respective time‐points. Conclusion: Salvage cystectomy and IC can be safely performed as a last‐line treatment for benign conditions and increases general HRQOL in the long‐term follow‐up. Thus, it can play a role in a holistic approach for a challenging clinical setting.